Astronomy - Tabanli, Mustafa (New Jersey : Everest Production, 2008)
As Above, So Below: Man's Quest to Seek Answers in the Heavens. Since the beginning of human history, we have looked up toward the sky with wonder and curiosity seeking not only answers to questions about the universe but also clues about how we fit into the grand picture. In this program, leading thinkers explore the science of astronomy and our relentless fascination with the heavens and what we have learned along the way about the planets, the stars, and ourselves.
Executive producer, Nasuhi Yurt.
Host : MaryLynn Schiavi.
DVD format.
Keywords: Astronomy